Evaluation of E. coli inhibition by plain and polymer-coated silver nanoparticles - Ashmore, D'Andrea; Chaudhari, Atul; Barlow, Brandi; Barlow, Brett; Harper, Talia; Vig, Komal; Miller, Michael; Singh, Shree; Nelson, Edward; Pillai, Shreekumar (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
Escherichia coli causes various ailments such as septicemia, enteritis, foodborne illnesses, and urinary tract infections which are of concern in the public health field due to antibiotic resistance. Silver nanoparticles (AgNP) are known for their biocompatibility and antibacterial activity, and may prove to be an alternative method of treatment, especially as wound dressings. In this study, we compared the antibacterial efficacy of two polymer-coated silver nanoparticles either containing 10% Ag (Ag 10% + Polymer), or 99% Ag (AgPVP) in relation to plain uncoated silver nanoparticles (AgNP). Atomic force microscopy was used to characterize the nanoparticles, and their antibacterial efficacy was compared by the minimum inhibitory concentration (MIC) and bacterial growth curve assays, followed by molecular studies using scanning electron microscopy (SEM) and (qRT- PCR). AgNP inhibited the growth of E. coli only at 0.621 mg/mL, which was double the concentration required for both coated nanoparticles (0.312 mg/mL). Similarly, bacterial growth was impeded as early as 8 h at 0.156 mg/mL of both coated nanoparticles as compared to 0.312 mg/mL for plain AgNP. SEM data showed that nanoparticles damaged the cell membrane, resulting in bacterial cell lysis, expulsion of cellular contents, and complete disintegration of some cells. The expression of genes associated with the TCA cycle (aceF and frdB) and amino acid metabolism (gadB, metL, argC) were substantially downregulated in E. coli treated with nanoparticles. The reduction in the silver ion (Ag+) concentration of polymer-coated AgNP did not affect their antibacterial efficacy against E. coli.